2019
DOI: 10.15845/noril.v11i1.2787
|View full text |Cite
|
Sign up to set email alerts
|

Information Seeking MOOCs at the University of Helsinki

Abstract: The University of Helsinki is a multidisciplinary university with about 31 300 students and 7800 staff. Our bachelor’s and master’s degree programmes were recently redesigned and started off in the autumn semester 2017. At the Helsinki University Library, this led to the reorganization of our information literacy teaching in order to be able to connect with larger amounts of students. In autumn 2017, we launched two new MOOCs: a Finnish language one for bachelor’s level and an English version mainly for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Several studies [5,26,41,[44][45][46][47][48][49][50][51] demonstrated that during rupture in tensile testing of paper, some fibres pull out and others break. Beating weakens the fibres and the proportion of broken fibres during paper testing increases with the beating level.…”
Section: Impact Of Fibre Strength On the Development Of Paper Propertiesmentioning
confidence: 99%
“…Several studies [5,26,41,[44][45][46][47][48][49][50][51] demonstrated that during rupture in tensile testing of paper, some fibres pull out and others break. Beating weakens the fibres and the proportion of broken fibres during paper testing increases with the beating level.…”
Section: Impact Of Fibre Strength On the Development Of Paper Propertiesmentioning
confidence: 99%